The Routledge international handbook of human aggression: current issues and perspectives - Ireland, Jane L.; Birch, Philip; Ireland, Carol A. (The Routledge international handbook series, 2022)
Drawing upon international expertise, and including some of the most well-known academics and practitioners in the field, The Routledge International Handbook of Human Aggression is the first reference work to fully capture how our understanding of aggression has been refined and reconceptualised in recent years. Divided into five sections, the handbook covers some of the most interesting and timely topics within human aggression research, with analysis of both indirect and direct forms of aggression, and including chapters on sexual aggression, workplace bullying, animal abuse, gang violence and female aggression. It recognises that, in many cases, aggression is an adaptive choice rather than a moral choice. Providing practitioners and academics with an up-to-date resource that covers broad areas of interest and application, the book will be essential reading for students, researchers and practitioners associated with a range of social science disciplines, including psychology, criminology, social work and sociology, particularly those with an interest in developmental, organisational, forensic and criminal justice allied disciplines